2019
DOI: 10.1111/1467-8268.12408
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Implications of Continental Free Trade Area: A Short‐run Perspective of Malawi

Abstract: The study estimates, in the short run, the tax revenue implications of Malawi joining the African Continental Free Trade Area (AfCFTA) using liberalization approaches and the SMART Model. The results show that Malawi is likely to benefit from joining the AfCFTA through trade creation. However, revenue losses are imminent and more pronounced for capital goods. The study recommends that Malawi should join the AfCFTA and liberalize while keeping a substantial portion of tariff lines for sensitive products and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…In both scenarios, the socio-economic gains outweigh the loss of tariff revenue for the whole of Africa. This is in line with the results of the study of Masiya (2019) in Malawi.…”
supporting
confidence: 92%
“…In both scenarios, the socio-economic gains outweigh the loss of tariff revenue for the whole of Africa. This is in line with the results of the study of Masiya (2019) in Malawi.…”
supporting
confidence: 92%
“…Thus, for most part, while evidence abounds on the sub-regional trade agreements spurring trade, empirical studies on the trade effects of a continental-wide trade agreement, such as AfCTFA, is dearth although few studies are notable. For instance, Masiya (2019) examines the short-run revenue implications of AfCFTA for Malawi and finds that, while the country stands to benefit from ratifying the AfCFTA agreement through improved trade creation, the country will undoubtedly lose tax revenue with more marked effects stemming from the elimination of tariffs on capital goods. More recently, Abrego et al (2019) estimate the welfare effects of the AfCFTA for 45 countries in Africa and find significant potential welfare gains from trade liberalization.…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that total tax revenue as a share of GDP declined because of the inability of Tanzania to strengthen the domestic taxes as a means of recovering from customs revenue loss due to liberalization. This result is also shared by Masiya (2019) in analyzing the potential revenue implications of AfCFTA in Malawi using SMART model. Masiya (2019) has observed that Malawi is likely to benefit from joining the AfCFTA through trade creation.…”
Section: Literature Reviewmentioning
confidence: 53%
“…This result is also shared by Masiya (2019) in analyzing the potential revenue implications of AfCFTA in Malawi using SMART model. Masiya (2019) has observed that Malawi is likely to benefit from joining the AfCFTA through trade creation. However, revenue losses are imminent and more pronounced for capital goods.…”
Section: Literature Reviewmentioning
confidence: 53%
See 1 more Smart Citation